Molecular Mechanisms of the 1-Aminocyclopropane-1-Carboxylic Acid (ACC) Deaminase Producing Trichoderma asperellum MAP1 in Enhancing Wheat Tolerance to Waterlogging Stress - Rauf, Mamoona; Awais, Muhammad; Ud-Din, Aziz; Ali, Kazim; Gul, Humaira; Rahman, Muhammad Mizanur; Hamayun, Muhammad; Arif, Muhammad (Frontiers in Plant Science, 2021)
Waterlogging stress (WS) induces ethylene (ET) and polyamine (spermine, putrescine, and spermidine) production in plants, but their reprogramming is a decisive element for determining the fate of the plant upon waterlogging-induced stress. WS can be challenged by exploring symbiotic microbes that improve the plant’s ability to grow better and resist WS. The present study deals with identification and application of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase-producing fungal endophyte Trichoderma asperellum (strain MAP1), isolated from the roots of Canna indica L., on wheat growth under WS. MAP1 positively affected wheat growth by secreting phytohormones/secondary metabolites, strengthening the plant’s antioxidant system and influencing the physiology through polyamine production and modulating gene expression. MAP1 inoculation promoted yield in comparison to non-endophyte inoculated waterlogged seedlings. Exogenously applied ethephon (ET synthesis inducer) and 1-aminocyclopropane carboxylic acid (ACC; ET precursor) showed a reduction in growth, compared to MAP1-inoculated waterlogged seedlings, while amino-oxyacetic acid (AOA; ET inhibitor) application reversed the negative effect imposed by ET and ACC, upon waterlogging treatment. A significant reduction in plant growth rate, chlorophyll content, and stomatal conductance was noticed, while H2O2, MDA production, and electrolyte leakage were increased in non-inoculated waterlogged seedlings. Moreover, in comparison to non-inoculated waterlogged wheat seedlings, MAP1-inoculated waterlogged wheat exhibited antioxidant–enzyme activities. In agreement with the physiological results, genes associated with the free polyamine (PA) biosynthesis were highly induced and PA content was abundant in MAP1-inoculated seedlings. Furthermore, ET biosynthesis/signaling gene expression was reduced upon MAP1 inoculation under WS. Briefly, MAP1 mitigated the adverse effect of WS in wheat, by reprogramming the PAs and ET biosynthesis, which leads to optimal stomatal conductance, increased photosynthesis, and membrane stability as well as reduced ET-induced leaf senescence.